2013
DOI: 10.1590/s0034-8910.2013047003377
|View full text |Cite
|
Sign up to set email alerts
|

Consumo alimentar e fatores dietéticos envolvidos no processo saúde e doença de Nikkeis: revisão sistemática

Abstract: OBJETIVO: Analisar consumo alimentar e fatores dietéticos envolvidos no processo saúde e doença da população de nikkeis.MÉTODOS: Foi realizada revisão sistemática da literatura, com buscas nas bases de dados do Lilacs, SciELO e PubMed/Medline, referente ao período de 1997 a 2012, de estudos observacionais sobre o consumo alimentar de nikkeis. Inicialmente, foram analisados 137 títulos e resumos, sendo excluídos estudos de intervenção, aqueles que apresentavam somente níveis séricos de vitaminas e metabólitos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…The "fast food snacks" pattern, including soft drinks, sweets, cakes, cookies, salted snacks, processed meats, and other high-fat products, also identified in other studies 47,49,50,51 , showed positive and moderate associations in all the target pairs. This finding may indicate the Westernization of eating habits in the family, since this pattern consists of foods that are high in fat, sugar, and salt, reflecting the incorporation of unhealthy habits and customs related to the Western lifestyle 52,53,54,55 , especially in Brazilian families with adolescent children, given that consumption of such foods is more prevalent in this age bracket 48 . This dietary pattern has been associated with an increase in metabolic disorders and weight gain in both adolescence 47,56,57 and adulthood 55,58,59,60,61 .…”
Section: Discussionmentioning
confidence: 94%
“…The "fast food snacks" pattern, including soft drinks, sweets, cakes, cookies, salted snacks, processed meats, and other high-fat products, also identified in other studies 47,49,50,51 , showed positive and moderate associations in all the target pairs. This finding may indicate the Westernization of eating habits in the family, since this pattern consists of foods that are high in fat, sugar, and salt, reflecting the incorporation of unhealthy habits and customs related to the Western lifestyle 52,53,54,55 , especially in Brazilian families with adolescent children, given that consumption of such foods is more prevalent in this age bracket 48 . This dietary pattern has been associated with an increase in metabolic disorders and weight gain in both adolescence 47,56,57 and adulthood 55,58,59,60,61 .…”
Section: Discussionmentioning
confidence: 94%
“…is instrument is used for quality assessment of observational studies and randomized clinical studies and comprises 27 items totalling up to 32 points (higher scores indicating superior quality). In this review, a modified version [22][23][24][25][26][27][28] of this instrument was used which consisted of 17 items (1-3, 5-7, 9-11, 16-18, 20-22, and 25-26), totalling up to a maximum of 17 points. e relevant domains for the instrument included description, external validity, and internal validity (confusion/ selection bias).…”
Section: Bias Risk Assessmentmentioning
confidence: 99%